Lion (Panthera leo) ecology and survival in protected areas of Ethiopia - Yirga, G; Amare, S; Gebresenbe, F; de Longh, HH; Vos, M; Sillero-Zubiri, C; Bauer, H (Springer, 2021)
Ethiopia is renowned for its cultural and biological diversity and covers an important share of lion habitat in Africa, providing connectivity between East and Central Africa. The aim of this study was to investigate the status of lions and human-lion conflict in several protected areas of Ethiopia; and to present an overview on lion distribution nationally. We used call-ups and semi structured interviews with 809 randomly selected pastoralists to investigate human-lion conflict and pastoralist perceptions towards lions in five priority sites and collected further anecdotal information for all other known or possible lion range. We had chance encounters with six lions, but we observed no lion responses to the call-ups. We recorded 145 spotted hyaena and 23 jackal responses at respectively 25 and 13 of the 46 call-up stations. Overall, respondents viewed lions as dangerous carnivores, but nonetheless responded that lions should be present regionally, preferably in restricted areas. Most respondents disagreed that the killing of lions should be allowed, but we note that a small minority strongly agreed to killing. A large majority of respondents agreed that more people need to be given information about lions. Respondents mentioned spotted hyaena and leopard as the main predators on all livestock followed by jackal (shoats) and lion (mainly cattle). The impact of depredation on livestock mortality was nearly twice that of disease. Our results strongly suggest that lion densities are low and may have substantially decreased in Awash, Nechisar, Chebera-Churchura, and Mago National Parks and in Kaffa Biosphere Reserve due to conflict, habitat loss and especially ineffective protection. Anecdotal information suggests that lions are widespread but rare and that there is no stronghold in Ethiopia. Considering the unique evolutionary background of Ethiopia as the bridge between Central and East African lion populations, and the significant role of the lion in Ethiopian history and culture, we argue that more emphasis should be given to the protection of prioritized lion populations.